Breaking barriers: Adjunctive use of the Ontario Telemedicine Network (OTN) to reach adolescents with obesity living in remote locations. (June 2020) - Coles, Nicole; Patel, Barkha P; Li, Ping; Cordeiro, Kristina; Steinberg, Alissa; Zdravkovic, Ana; Hamilton, Jill K
Introduction: Implementation of telemedicine has been shown to improve health outcomes, such as body mass index (BMI). However, it is unclear whether telemedicine is useful alongside traditional weight-management programmes for adolescents with complex obesity. The objective was to evaluate implementation of the Ontario Telemedicine Network (OTN), a videoconferencing programme, as an adjunctive tool to face-to-face counselling within the setting of an established interdisciplinary obesity treatment programme. Methods: Our observational cohort included two groups of adolescents enrolled in a clinical obesity-management programme over a two year period. Adolescents ( n = 50) in group 1 attended both in-person and virtual visits (OTN group), and adolescents ( n = 50) in group 2 received only in-person visits (comparison group). Within the OTN group, satisfaction survey responses were compared between patients and healthcare professionals. Change in BMI per month, paediatric quality of life scores, session attendance and demographic variables were compared between groups. Results: OTN subjects averaged 4.9 telehealth visits per adolescent over the two year programme. Both OTN and comparison groups had similar changes in BMI ( p = 0.757), with increases over time ( p = 0.042). Paediatric quality of life scores in both groups improved over time compared to baseline ( p < 0.001), with higher scores for children compared to parental-reported child scores ( p = 0.008). Both adolescents and healthcare professionals using the OTN were similarly satisfied with their experience. Conclusion: Adjunctive use of the OTN within the setting of a weight-management programme is feasible, well accepted by families and healthcare providers, and led to similar outcomes compared to usual care.